A luta na terra: a pluriatividade e multifuncionalidade como alternativas de permanência no campo aos assentados de Zumbi dos Palmares - MT - Oliveira, Iolanda Lopes de (2016)
The dynamics of geographical space becomes more and more complex and changeable, and one of its effects is well known in the population living in rural areas spreading on diversification of agricultural and non-agricultural occupations (pluriactivity) as well as the new tasks assigned to rural and agriculture, which are consolidated in addition to farming. The increase of the phenomenon of non-agricultural activities in rural areas makes these activities no longer to be associated only to the agricultural, inducing farmers to develop "new" economic and social functions. With increased interest to the rural "world", there is a complexity of technical objects and actions in the field, that is bringing the need to seizure the multiple functions of agriculture. (multifunctionality). The research aims to analyze the pluriactivity and multifunctionality as alternatives in the process of battle "in the" land of the settlers called Zumbi dos Palmares in the state of Mato Grosso. The settlement located in the city of Dom Aquino, southeast region of the state, was set at a location where conditions do not allow further development, hindering social and economic reproduction of family plots. Therefore, the alternatives analyzed enable the supplementary income and hence the stay of families in settlement plots, keeping life and reproduction, even in a precarious way and far from infrastructure for market access, technical assistance, health care and education assistance.